2016
DOI: 10.1590/1413-812320152112.16682015
|View full text |Cite
|
Sign up to set email alerts
|

Completitude das notificações de violência perpetrada contra adolescentes em Pernambuco, Brasil

Abstract: Resumo O objetivo deste trabalho foi analisar a tendência da completitude dos dados de violência perpetrada contra adolescentes registrados em Pernambuco, em 2009-2012. Estudo transversal, com 5.259 adolescentes vítimas de violência notificadas no SINAN-VIVA da Secretaria Estadual de Saúde de Pernambuco. Utilizou regressão linear simples para investigar a tendência de completitude das variáveis. Os percentuais de completitude foram considerados como variáveis dependentes (Y) e os anos da série, como independen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
24

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 18 publications
0
7
0
24
Order By: Relevance
“…Santos et al 34 analisaram as notificações de violência contra adolescentes em Pernambuco, de 2009 a 2012, segundo os critérios de Romero e Cunha 32 , tendo encontrado dados de qualidade ruim e muito ruim. Os autores mencionaram a fragilidade na qualidade dos dados nos SIS, em especial com relação à completitude das informações, e a importância dessa avaliação no SINAN VIVA.…”
Section: ▄ Discussãounclassified
See 1 more Smart Citation
“…Santos et al 34 analisaram as notificações de violência contra adolescentes em Pernambuco, de 2009 a 2012, segundo os critérios de Romero e Cunha 32 , tendo encontrado dados de qualidade ruim e muito ruim. Os autores mencionaram a fragilidade na qualidade dos dados nos SIS, em especial com relação à completitude das informações, e a importância dessa avaliação no SINAN VIVA.…”
Section: ▄ Discussãounclassified
“…Os 307 casos de violência contra mulheres residentes em Niterói analisados neste estudo apresentaram perfil similar ao encontrado em outras pesquisas, como maior frequência de violência entre as mais jovens, sem companheiro, na residência, com predomínio de violência física, psicológica/moral e sexual, além de registros de negligência entre adolescentes e idosas 2,24,25,34,[36][37][38][39][40][41][42] .…”
Section: ▄ Discussãounclassified
“…The most common forms of violence against children are neglect and abandonment, and physical, psychological, and sexual violence, while violence is predominantly committed by parents within the home 13 . The most common form of violence against adolescents is physical violence (assault) inside and outside the home, often committed by strangers and particularly associated with inequality and the use of alcohol and other drugs 8,14 .…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the continuous monitoring of external causes and violence against adolescents is essential for effective policy implementation 14 . However, studies of violence in this age group tend to be qualitative 9,12 , rely on hospital admission and mortality databases 11 , and focus on the local level 13 and, as a result, national studies of violence in this age group remain scarce.…”
Section: Introductionmentioning
confidence: 99%
“…A similar result was found by a previous study, conducted in Pernambuco, in which the authors indicated regular completeness of the fields intended to characterize violence (time of incident, place, recurrence, type of violence, type of aggression) and to characterize the probable perpetrator (sex, relationship with the victim), 29 and very low completeness for the following variables: schooling, time of incident and use of alcohol by the perpetrator. 30 It appears to be pertinent that the importance of this information for violence sur-Nathália França de Oliveira et al veillance should be continually emphasized in health services throughout Brazil, since low completeness of the fields relating to them reduces not only the performance of municipal surveillance, but also hinders the development of specific actions aimed both at reducing case occurrence and also at case follow-up.…”
Section: Discussionmentioning
confidence: 99%